Multifocal osteoclastoma of the skull: case report - Ricardo Souza Quadros; Atos Alves de Sousa; Gervásio Telles Cardoso Carvalho; Marcos Antônio Dellaretti Filho (Arquivos de Neuro-Psiquiatria)
We describe the case of a 35 years old man with a nonspecific complaint of a slow growing solid mass in the frontal region. Radiological exams evidenced two more lesions : in the superior and lateral walls of the orbit. Treated with total excision of the lesions and a cranioplastic procedure at the same act, with favorable outcome. Microscopic findings suggested giant cell tumor in the three lesions that was confirmed by imunohistochemical examination.